Willingness to trade-off years of life for an HIV cure – an experimental exploration of affective forecasting - Ilona Fridman; Nir Eyal; Karen A. Scherr; Judith S. Currier; Kenneth A. Freedberg; Scott D. Halpern; Daniel R. Kuritzkes; Monica Magalhaes; Kathryn I. Pollak; Peter A. Ubel (AIDS Research and Therapy, 2024)
Abstract Background In the US, 1.2 million people live with HIV (PWH). Despite having near-normal life expectancies due to antiretroviral therapy (ART), many PWH seek an HIV cure, even if it means risking their lives. This willingness to take risks for a cure raises questions about “affective forecasting biases,” where people tend to overestimate the positive impact of future events on their well-being. We conducted a study to test two interventions to mitigate affective forecasting in the decisions of PWH about taking HIV cure medication. Methods We recruited PWH to complete a 30-minute survey about their current quality of life (QoL) and the QoL they anticipate after being cured of HIV, and assigned them to either no additional intervention, to one of two interventions intended to reduce affective forecasting bias, or to both interventions: (1) a defocusing intervention designed to broaden the number of life domains people consider when imagining life changes associated with new circumstances (e.g. HIV cure); and (2) an adaptation intervention to help them gauge fading of strong emotions over time. The study design included a 2 × 2 design: defocusing (yes/no) x adaptation (yes/no) intervention. We assessed PWH’s willingness to take hypothetical HIV sterilizing cure medication using the Time Trade-Off (TTO) and their quality of life predictions with WHOQOL-HIV. Results 296 PWH participated. Counter to what we had hypothesized, neither intervention significantly reduced PWH’s willingness to trade time for a cure. Instead, the defocusing intervention increased their willingness to trade time (IRR 1.77, p = 0.03). Exploratory analysis revealed that PWH with lower current quality of life who received the defocusing intervention were more willing to trade time for a cure. Conclusion These negative findings suggest that either these biases are difficult to overcome in the settings of HIV curative medication or other factors beyond affective forecasting biases influence willingness to participate in HIV curative studies, such as respondents’ current quality of life.